Program Guru Tamu SMK N 1 Sragi: Pelatihan Digital Branding Guna Membangun Identitas Merek di Era Digital - Pratama, Versiandika Yudha; Taufiq Abadi, Muhammad; Syamsuddin; Muasomah; Arya Putra, Muhammad; Hidayati, Taufiq (ADM : Jurnal Abdi Dosen dan Mahasiswa, 2025)
Digital branding has become an important element in building a strong brand identity amidst the challenges of the digital era. The guest teacher-based community service program at SMK Negeri 1 Sragi aims to provide education and training on digital branding strategies to students who want to become entrepreneurs. This activity involves materials on building brand identity, creating logos, producing digital content, and using Content Management Systems (CMS). With a practical and interactive approach, students are invited to understand the concept and apply digital branding strategies in their businesses. Program evaluations show students' success in creating logos and digital content, as well as a deep understanding of the importance of brand identity in the digital era. Participant testimonials confirm the benefits of this program in improving students' skills and readiness to face competition in the digital business world. This program is a strategic step in developing students' competencies and strengthening their potential as future entrepreneurs.